PENGARUH STRESOR DAN MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan Kantor PT. Telekomunikasi Indonesia Tbk. Divisi Regional IV Wilayah Jateng dan D.I. Yogyakarta) - Sabda, Yehezkiel Abdi; Darmastuti, Ismi (Faculty of Economics and Business Diponegoro University, 2015)
This research is motivated by the research gap from previous studies, and it is known that there is a decline in the performance of employees. This study aims to analyze the effect of stressors and motivation on employee performance, and organizational commitment as an intervening variable. Data were collected from a sample of 76 respondents, who work as employees at PT. Telekomunikasi Indonesia Tbk. Regional Division IV Central Java-Yogyakarta. Analysis of the data in this study using multiple linear regression techniques, and sobel test, to test the mediating effect, using SPSS program.The results showed, stressors variable negatively affect organizational commitment and performance of employees. Motivation positively affect on organizational commitment. Motivation and organizational commitment has positive influence on employee performance. Organizational commitment is a good mediating variable between stressors and motivation on employee performance. The coefficient for total determination in this study is 86.5%.